The process of the modern tragic hero in Latin American narrative - Cabanillas-Quispe, Jorge (2025)
The purpose of this article is to establish the processes of the modern Latin American tragic hero in four novels by the writer Gabriel García Márquez: One Hundred Years of Solitude, Love in the Time of Cholera, Of Love and Other Demons, and Chronicle of a Death Foretold. To this end, their relationship with the period and historical context was identified. Based on different analyses and texts that describe the characteristics of archiving and narratology: the historical in literature, the registry, and the archive. The methods employed were inductive-deductive, narratology, historical analysis, and hermeneutics, through which the research hypothesis was demonstrated: that the process of the tragic hero in Latin America is closely related to the historical context and the construction of identity, as evidenced by the results. In conclusion, the simultaneous study of the novels with their historical, cultural, and social environment is necessary.